Effect of the reactive blend conditions on the thermal properties of waste biomass and soft coal as a reducing agent for silicon production. (March 2022) - Zhang, Hongmei; Chen, Zhengjie; Ma, Wenhui; Cao, Shijie
Abstract: The reducing agents used for industrial silicon production often suffer from high coking and high consumption of coal, which is associated with high energy consumption, low efficiency, and low output. To overcome these issues, a mixture of biomass and soft coal (SC) was investigated as a new type of carbonaceous reducing agent for industrial silicon production. In this paper, TGA, SEM, XRD, and Raman spectroscopy were used to study the effects of the different proportions of banana peel (BP) and SC on the activity of carbon materials under different fermentation conditions and molding times. The results showed that the pyrolysis temperatures of fermented mixed carbon materials were decreased by 38–55 °C, and the activation energy was reduced by 68–74%. The pyrolysis temperature and activation energy of moldy mixed carbon materials decreased by 49–94 °C and 46–51%. There was a significant synergistic effect between the carbon materials, and the reactivity of SC was increased. The reduction of silica by fermented carbon materials was better than moldy carbon materials; therefore, the fermentation conditions were more conducive to the preparation of carbonaceous reducing agents for the production of industrial silicon.